Determinants of Profitability and its Implications on Corporate Values (Studies at Ceramic, Porcelain and Glass Sub Sector Listed in Indonesia Stock Exchange, 2009 - 2018) - Mulyana, Bambang; Adidarma, Benis (International Journal of Business, Economics and Management, 2020)
This study aims to analyse the effects on the profitability (return on assets) and its implications on corporate value by internal influences (current ratio, leverage and sales growth) and external influences (IDR exchange rate and energy price). The object of research is ceramics, porcelain and glass industries registered in the Indonesian stock exchange with total 8 industries in the period 2009 – 2018. The methodology used is descriptive quantitative research and causality with purposive sampling technique and panel data regression analysis. The result of the study indicated that liquidity and energy price did not have a significant negative effect on profitability, leverage had a significant negative effect on profitability, sales growth had a significant positive effect on profitability, and IDR change rate did not have a significant positive effect on profitability. While profitability has significant positive effect on corporate value.